The Tanner lectures on human values vol. 3 - Rawls, John; McMurrin, Sterling M. (Cambridge : Cambridge University Press, 2011)
The Tanner Lectures, founded to reflect on scholarly and scientific perspectives on human values, are held annually at universities worldwide. Volume III delves into the potential practical applications of various theoretical approaches to addressing the significant issues of values and the challenges faced by modern society.
1. The basic liberties and their priority John Rawls; 2. Is liberty possible? Charles Fried; 3. The representative arts as a source of truth John Passmore; 4. A writer from Chicago Saul Bellow; 5. Drugs and the brain and society Solomon H. Snyder; 6. The arms race Joan Robinson
Includes index.
Keywords: Values